Bacteriophages as a Strategy to Protect Potato Tubers against Dickeya dianthicola and Pectobacterium carotovorum Soft Rot - Beňo, Filip; Horsáková, Iveta; Kmoch, Martin; Petrzik, Karel; Krátká, Gabriela; Ševčík, Rudolf (Microorganisms, 2022)
The protective effect of bacteriophage suspensions (Ds3CZ + Ds20CZ and PcCB7V + PcCB251) on phytopathogenic bacteria causing soft rot of potato tubers, namely Dickeya dianthicola (D50, D200) and Pectobacterium carotovorum (P87, P224), was observed in ex vivo and in vitro experiments. Ex vivo tests were performed (with air access) on potato slices, on cylindrical cuts from the center of the tubers, and directly in whole potato tubers. In vitro experiments were carried out in a liquid medium using RTS-8 bioreactors, where bacterial growth was monitored as optical density. In particular, the inhibitory effects of phages were confirmed in experiments on potato slices, where suppression of rot development was evident at first glance. Phage treatment against selected bacteria positively affected potato hardness. Hardness of samples treated with bacteria only was statistically significantly reduced (p < 0.05 for D50 and p < 0.001 for D200 and P87). Ex vivo experiments confirmed significant inhibition of P87 symptom development, partial inhibition of D200 and D50 in phage-treated tubers, and no effect was observed for P224. The inhibitory effect of phages against bacteria was not observed in the in vitro experiment.
Keywords: phage control; Dickeya dianthicola; potato tubers; Pectobacterium carotovorum; soft rot